The Consequences of Love - Addonia, Sulaiman, ....- (London : Vintage books, 2009)
It is summer in Jeddah but Naser's life seems bleak. An immigrant in an unfriendly land, his friends have fled town for cooler climes and left him to his dead-end job and the scrutiny of the religious police, who keep watch through the shaded windows of their government jeeps. He spends his time writing to his mother in Africa and yearning to meet a woman - but in a country that separates men and women with walls and veils he feels increasingly trapped. Then, one of the black-clad women drops a piece of paper at his feet, instructing him to follow her pink shoes and suddenly his black-and-white life blooms into colour. But relationships between unmarried men and women are illegal under the strict Wahhibism of Saudi state rule - and it's not long before their forbidden love must face the hardest test of all...
Keywords: Islam en sexualiteit; Onmogelijke liefde; Roman